Strategi Pengawasan Partisipatif untuk Mendukung Pengembangan Desa Wisata Paranggupito, Kabupaten Wonogiri - Awang Febrian Pangestu; Sukarti Sukarti (Lembaga Pengembangan Kinerja Dosen, 2026)
The purpose of this study is to analyze the strategies employed by the Wonogiri Regency Election Supervisory Agency (Bawaslu) in implementing participatory oversight in Paranggupito Subdistrict, while also examining how these strategies intersect with efforts to empower the community as a tourism village. The study uses a descriptive qualitative approach, with data collected through interviews and document analysis. The results show that the Wonogiri Regency Bawaslu implemented two main strategies: partnering with educational institutions by signing a Memorandum of Understanding (MoU) with Pancasila 3 High School in Paranggupito; and designating Gudangharjo Village as a Participatory Oversight Village while involving local youth in outreach activities during cultural events. This study also found a two-way relationship between participatory oversight and the life of the tourism village: on the one hand, the character of the tourism village community facilitates the dissemination of oversight values, and on the other hand, residents’ involvement in election oversight helps foster a sense of trust and openness, which also serves as an important asset for the management of the tourism village itself. In other words, the trust and organizational habits that have grown out of this participatory oversight program ultimately help sustain the Paranggupito tourism village. This study concludes that the sustainability of both of these aspects depends heavily on the consistency of Bawaslu’s guidance and the government’s long-term commitment.